Thyme Plant Powder (Thymus vulgaris) Improves the Production Performance of Laying Hens by Affecting Ovarian Follicles - Ebrahimi, M.; Ghaderi Chaparabad, H.; Al-Moussawi, I. S. M.; Hosseini, M. H.; Mirghelenj, S. A. (Tropical Animal Science Journal, 2025)
The present experiment investigated the effects of different levels of thyme powder on performance, blood biochemical parameters, reproductive system morphometry, and egg quality traits at different storage temperatures in old laying hens. For this purpose, in a completely randomized design, 144 laying hens (Hy-line-W36) aged 65 weeks were assigned to 3 treatments, 6 replications, and 8 birds each. Experimental diets were corn-soy based, including 0%, 0.25%, and 0.5% thyme powder (TP). At the end of the experimental period (8th week of the experiment), 6 eggs were selected from each replicate and kept at temperatures of 4 and 25 °C for 30 days to determine the internal quality. The results showed that the egg weight of birds fed with diets containing 0.25% and 0.5% TP was significantly higher than control ones (p